The Development of Tutorial Videos to Improve Learning Outcome of Islamic Education Students - Ilmudinulloh, Rafiud; Ahmad Bustomi; Widya Rizky Pratiwi (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2025)
The presence of appropriate learning media is needed in practical courses, especially with only 2 credits. Lecturers and students are aware of this, but there has been no serious effort to realize this hope. As a result, learning becomes ineffective and student learning outcomes are low. Responding to this problem, the researcher aims to develop a video tutorial that is suitable for use in the Fiqih Ibadah course to improve student learning outcomes. This study uses 4D development design which consists of defining, designing, developing, and disseminating. Data analysis techniques use test instruments to examine the increase in learning outcomes and questionnaires to test the feasibility of video tutorial. Questionnaire data were analyzed using descriptive statistical formulas, and learning achievement test data were analyzed using the N-gain formula. The results of this study indicate that video tutorials get a good predicate or 4.3 from the media expert, a very good predicate or 4.9 from a material expert, as well as a very good predicate or 4.6 from students, and student learning outcomes obtain an N-gain of 0.6 in the moderate or quite effective category as seen from the average pretest score of 77.5 and the posttest average score of 90. So it can be concluded that video tutorials are appropriate for use in science courses and can improve student learning outcomes.